Cost-utility of cognitive behavioral therapy versus U.S. Food and Drug Administration recommended drugs and usual care in the treatment of patients with fibromyalgia: an economic evaluation alongside a 6-month randomized controlled trial - Luciano, Juan V; D'Amico, Francesco; Cerdà-Lafont, Marta; Peñarrubia-María, María T; Knapp, Martin; Cuesta-Vargas, Antonio; Serrano-Blanco, Antoni; Garcia Campayo, Javier (BMC Springer Nature, 2014)
Introduction: Cognitive behavioral therapy (CBT) and U.S. Food and Drug Administration (FDA)-recommended pharmacologic treatments (RPTs; pregabalin, duloxetine, and milnacipran) are effective treatment options for fibromyalgia (FM) syndrome and are currently recommended by clinical guidelines. Methods: The economic evaluation was conducted alongside a 6-month, multicenter, randomized, blinded, parallel group, controlled trial. In total, 168 FM patients from 41 general practices in Zaragoza (Spain) were randomized to CBT (n = 57), RPT (n = 56), or TAU (n = 55). The main outcome measures were Quality-Adjusted Life Years (QALYs, assessed by using the EuroQoL-5D questionnaire) and improvements in health-related quality of life (HRQoL, assessed by using EuroQoL-5D visual analogue scale, EQ-VAS). The costs of healthcare use were estimated from patient self-reports (Client Service Receipt Inventory). Results: On average, the total costs per patient in the CBT group (1,847 €) were significantly lower than those in patients receiving RPT (3,664 €) or TAU (3,124 €). Patients receiving CBT reported a higher quality of life (QALYs and EQ-VAS scores); the differences between groups were significant only for EQ-VAS. From a complete case-analysis approach (base case), the point estimates of the cost-effectiveness ratios resulted in dominance for the CBT group in all of the comparisons performed, by using both QALYs and EQ-VAS as outcomes. These findings were confirmed by bootstrap analyses, net-benefit curves, and CEACs. Two additional sensitivity analyses (intention-to-treat analysis and per-protocol analysis) indicated that the results were robust. Conclusions: Because of lower costs, CBT is the most cost-effective treatment for adult FM patients. Implementation in routine medical care would require policymakers to develop more-widespread public access to trained and experienced therapists in group-based forms of CBT.
Keywords: Enfermos de fibromialgia - Asistencia sanitaria - Aspectos económicos; Analgesics; therapeutic use; Cognitive Behavioral Therapy; Fibromyalgia; therapy